A constitutive model of shape memory polymers based on glass transition and the concept of frozen strain release rate. (1st October 2017) - Li, Yunxin; Hu, Jianying; Liu, Zishun
Abstract: Shape memory polymers (SMPs) are a type of polymeric smart material. They can maintain a deformed shape and return to their original shape according to external stimuli, such as temperature, light, pH, magnetic field and so on. In the last decade, SMPs have gained increasing attention due to their unique properties and have thus led great progress in developing proper constitutive models. In this paper, we propose and establish a new phase-evolution-based thermomechanical constitutive model for amorphous SMPs by considering the materials as a mixture of the rubbery phase and glassy phase. The shape memory effect (SME) is captured under the assumption that the rubbery phase can transform into the glassy phase and that part of the strain will be frozen during the glass transition. To make the model be more feasible, furthermore, we improve the model by introducing a time factor and considering the influence of frozen strain release rate. To validate the robustness and applicability of the proposed new model, we reproduce the shape memory behaviors (SMBs) of two different materials under different constraints and conditions. The results show a remarkable consistency between the new model simulation and experimental data.